Thalamocortical Tracts, but not the Putamen, Present Microstructural Abnormalities in Juvenile Myoclonic Epilepsy: A Diffusion Tractography Study - Esmail, Eman H.; El Dein, Hadeel M. Seif; Yassine, Inas A.; Zakaria, Rania (Journal of Pediatric Epilepsy, 2018)
Background and Purpose The pathology of juvenile myoclonic epilepsy (JME) is related to thalamocortical dysfunction, and the putamen is closely related to the thalamocortical circuit. The purpose of this study is to evaluate the microstructure of the thalamo-cortico-striatal circuit in JME patients using diffusion tensor imaging (DTI).Materials and Methods This case–control study was conducted on 13 patients with JME (10 females and 3 males with a mean age of 23.38 ± 4.75 years) and 9 age- and sex-matched volunteers as control subjects. All subjects underwent DTI and conventional magnetic resonance imaging. The data were then processed via denoising, registration, and segmentation of the internal capsule and right and left putamen using the FMRIB Software Library (FSL). The FSL was also used to calculate the different anisotropy measures: the fractional anisotropy (FA), mean diffusivity (MD), longitudinal diffusivity (LD), and radial diffusivity (RD).Results The patients with JME had lower FA and higher LD in the thalamocortical tracts and lower MD in the frontal corticospinal tracts than the control subjects (p = 0.014, 0.001, and 0.04, respectively). No other significant differences were detected between the patients with JME and control subjects. The values measured in the right putamen were not significantly different from those measured in the left putamen in either the patients or controls.Conclusion This study demonstrates that microstructural abnormalities occur in the thalamocortical tracts but not the putamen of patients with JME. Nevertheless, microstructural asymmetry was not observed in the patients with JME.
Keywords: epilepsy; diffusion; fractional anisotropy; putamen; thalamocortical; white matter; asymmetry